Observations of Gravity Wave Refraction and Its Causes and Consequences. Issue 3 (6th February 2023) - Geldenhuys, M.; Kaifler, B.; Preusse, P.; Ungermann, J.; Alexander, P.; Krasauskas, L.; Rhode, S.; Woiwode, W.; Ern, M.; Rapp, M.; Riese, M.
Abstract: Horizontal gravity wave (GW) refraction was observed around the Andes and Drake Passage during the SouthTRAC campaign. GWs interact with the background wind through refraction and dissipation. This interaction helps to drive midatmospheric circulations and slows down the polar vortex by taking GW momentum flux (GWMF) from one location to another. The SouthTRAC campaign was composed to gain improved understanding of the propagation and dissipation of GWs. This study uses observational data from this campaign collected by the German High Altitude Long Range research aircraft on 12 September 2019. During the campaign a minor sudden stratospheric warming in the southern hemisphere occurred, which heavily influenced GW propagation and refraction and thus also the location and amount of GWMF deposition. Observations include measurements from below the aircraft by Gimballed Limb Observer for Radiance Imaging of the Atmosphere and above the aircraft by Airborne Lidar for the Middle Atmosphere. Refraction is identified in two different GW packets as low as ≈4 km and as high as 58 km. One GW packet of orographic origin and one of nonorographic origin is used to investigate refraction. Observations are supplemented by the Gravity‐wave Regional Or Global Ray Tracer, a simplified mountain wave model, ERA5 data and high‐resolution (3 km) WRF data. Contrary to some previous studies we find that refraction makes a noteworthy contribution in the amount and the location of GWMF deposition. This case study highlights the importance of refraction and provides compelling arguments that models should account for this. Plain Language Summary: Gravity waves (GWs) are very important for models to reproduce a midatmospheric circulations. But the fact is that models oversimplify the GW physics which results in GWs being underrepresented in models. GW refraction is one of the processes not captured by the physics in model parameterization schemes. This article uses high‐resolution observations from the SouthTRAC campaign to show how GWs refract and highlight the importance there‐of. This case study shows a 25% increase in the GWMF during propagation. The increase in momentum flux is linked to refraction which results in a shortening in the GW horizontal wavelength. This article shows that refraction is important for the amount as well as the location of GWMF deposition. This case study highlights the importance of refraction and provides compelling arguments that models should account for this. Key Points: A case study reveals that refraction results in a 25% increase in gravity wave momentum flux (GWMF) Including refraction dynamics affects the location of GWMF deposition Refraction is prominent in strong wind gradients (i.e., displaced vortex conditions)